Surface quality optimization of performance materials based on DLP printing technology - Sim, Hui Ying (Nanyang Technological University, 2024)
The rapid advancements in 3D Printing technology have enabled the development of many innovative products. Amongst the currently available technologies, digital light processing (DLP) which utilizes photopolymer resin as its material, is known for its superior surface finish and rapid production time. There are many types of photopolymers currently available, with prototyping resin being the most optimal selection for its surface quality. However, its poor mechanical properties limit its application to highly detailed concept models and not feasible for functional prototyping. In contrast, performance resins have good mechanical properties. Much research on performance resin has been on improving the mechanical properties, often with the surface quality not being the focus. As the mechanical performance of photopolymer is restricted by the materials used, improvements often require changing the formulation altogether. Conversely, surface quality of a printed part can be improved through optimising the parameters used or a slight modification to the formulation. As such, to obtain a DLP printed part that have a surface quality comparable to prototyping resin and industrially accepted mechanical properties, surface optimization will be done using performance resin. The objective of this research involved optimizing the surface quality of DLP printed parts through the optimization of the print parameters used and modification of resin composition with photoabsorber. Rhombicuboctahedron shape parts are printed with varying parameters (I.e. exposure time, waiting time and layer height) and is evaluated based on the surfaces corresponding to the 3 main axis (X, Y and Z). Surface measurements (Ra and Rt values) are taken using a surface profiler. Based on the Ra and Rt values obtained, the respective parameters are fine-tuned accordingly. Comparisons are made with benchmark from prototyping resin to determine whether the surface requirements are met. Results showed that it is possible to obtain a surface quality comparable to prototyping resin through the optimizing the printing parameter. Adjustments in the formulation also brought about positive changes in the surface quality.